The closer, the better? Processing relations between picture elements in historical paintings - Manuela Glaser; Manuel Knoos; Stephan Schwan (Journal of Eye Movement Research)
The present eye-tracking study investigated how audio explanations influence perception and the cognitive processing of historical paintings. Spatially close and distant pairs of picture elements and their semantic relations were named in an audio text either immediately after each other or with descriptions of other elements in between. It was assumed that the number of backward fixation counts on the first of the two mentioned related picture elements should be higher if they are spatially close rather than spatially distant. There should also be more backward fixation counts if the elements are named temporally close rather than temporally distant. Similar predictions were made for the retention of these picture elements and their relations. A 2x2x2 within-subject design (n=36) with spatial distance (close vs. distant), temporal distance (close vs. distant) and painting (Leutze vs. West) revealed more background fixation counts for spatially close compared to spatially distant elements but just for the Leutze painting. Accordingly, the relations between the spatially close pairs were retained better than between the spatially distant pairs in the Leutze painting but vice versa for the West painting. The results are discussed with regard to the spatial contiguity principle of multimedia learning and research on text coherence.